IMPLEMENTATION OF REPRODUCTIVE ABILITY OF FEMALE MINK OF SCANDINAVIAN TYPE SELECTION DEPENDING ON THE NUTRITIONAL STATUS - Яремич, Н. В. (Scientific Progress & Innovations, 2014)
A study of the reproductive parameters of female mink of different genotypes of Scandinavian selection based on their level of nutritional status at the time of the pairing season. For groups of mink of Scanglow and Pearl genotype maximum values recorded in female fertility index fatness was 23-25, and for the animals of Scanblack color type the figure was maximum under condition of increase of fatness index to 26-28. It was determined that the increase of fatness index for animals such as the Scandinavian brown color is correlated with decline in the proportion of stillbirths kits, and for pearl mink is typical increasing the size of the nest with a decreasing of the nutritional status of females.